A Study on the Zoning Method of Flash Flood Control for Mountainous Cities: A Case Study of Yunnan Province - Zhixiong Zhang; Qing Li; Changjun Liu; Yao Chen (Applied Sciences)
Flash floods are the most serious natural disasters in China and seriously affect its social and economic development. The transformation of the underlying surface caused by urbanization also brings new challenges to the prevention and control of flash flood disasters in mountainous cities. Based on the results of the flash flood disaster investigation and evaluation, this study calculated and examined the prevention and control zoning of flash flood threat areas in Yunnan, China, and determined the distribution of the prevention and control zoning of flash flood threat areas in each city in Yunnan Province. The results show that the key, medium, and general flash flood prevention and control zones in Yunnan Province account for 8%, 29%, and 63% of the total area, respectively. The areas of flash flood control that require attention are consistent with those of weak flash flood control reflected in the results of the flash flood disaster investigation and evaluation. By updating the results of flash flood disaster investigations and evaluations, the research method adopted in this study can be used to quickly update the results of flash flood prevention and control regionalization and improve the timeliness of flash flood disaster prevention and control.